Membaca Pendidikan Hadap-Masalah Paulo Freire dari Perspektif Intersubjektivitas menurut Merleau-Ponty - Julio Lorenzo Kapele; Antonius Baju Nujartanto (Sekolah Tinggi Filsafat Seminari Pineleng, 2026)
This article examines Paulo Freire’s problem-posing education through the perspective of intersubjectivity in Merleau-Ponty. The purpose of this study is to clarify the implicit intersubjective dimension within problem-posing education, which is not explicitly formulated by Freire but structurally present in his pedagogical framework. This research employs a qualitative method based on library research, using a hermeneutic approach to interpret Freire’s concept of education in dialogue with Merleau-Ponty’s phenomenology of the body, the presence of the other, and the language as the genesis of meaning. This study demonstrates that problem-posing education presupposes an understanding of human as embodied subjects who are always already open to others and to the world. Teacher-student relations are thus understood as subject-subject relations rather than hierarchical or objectifying ones. Language is not treated merely as technical instrument for transmitting, but as an expressive and constitutive medium through which meaning medium emerges intersubjectively. The main conclusion of this study shows that problem-posing education is grounded in an ontological dimension of intersubjectivity, where education is understood as an existential encounter between subjects who collectively disclose unfinished meanings in the world. This perspective offers a philosophical foundation for dialogical education and highlights its relevance for contemporary educational challenges.